Detrimental effect of antiepileptic drugs dose in pediatric children with epilepsy in Saudi Arabia: A prospective cohort study. Issue 26 (2nd July 2021) - Alotaibi, Badriyah S.; Alodhayani, Abdulaziz A.; Alwan, Ashraf; Alotaibi, Khalid Nijr; Melaiki, Brahim Tabarki; Almadhi, Aljawharah Mohammad; Alfares, Lulwah Haitham; Alalkami, Nahlah Ahmed
Abstract : Abstract: This study aims to evaluate the effect of dose titration for different oral antiepileptic medications among children with epilepsy in Riyadh, Saudi Arabia. A single-center prospective pilot, cohort study was undertaken at a tertiary hospital in Riyadh, Saudi Arabia. All medical records of pediatric patients below the age of 14 years of age who has been newly diagnosed with epilepsy by attending a medical specialist or on a new epileptic treatment plans were enrolled in the study. A total of 76 epileptic patients were screened for 3 months' period and 48 patients were included in this study. Out of the 48 patients, 31 patients followed the regular practice in the titration processes and 17 patients were in the British national formulary (BNF) guideline. Fifteen children who were on monotherapy of levetiracetam were in regular practice guideline experienced poor seizure control with a recorded number of seizure incidence (n = 10). The patient in regular practice guidelines using a combination therapy of phenytoin and levetiracetam were experiencing some behavioral disturbance and sedation effect. Seventeen patients followed in the BNF guideline who were on levetiracetam were experienced less adverse effect (n = 2) with no behavioral changes. The group who followed the regular practice found having a greater incidence of documented adverse effects compared to the patients following the BNF guideline. The titrating antiepileptic medication has a detrimental effect on the pediatric population as observed in this study. Abstract : Supplemental Digital Content is available in the text